Molecular Docking of Acetylacetone-Based Oxindole Against Indoleamine 2,3-Dioxygenase: Study of Energy Minimization - Josaphat, Frans; Fadlan, Arif (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
Molecular docking plays an essential role in drug discovery because it is more efficient and more affordable compared to traditional synthesis methods and biological assays. Molecular docking determines the conformation and affinity of non-covalent bonds between macromolecules (receptors) and small molecules (ligands) computationally. Energy minimization carried generally out by using the Merck Molecular Force Field 94 (MMFF94) force field produces ligands with the most stable conformation. MarvinSketch and Open Babel for energy minimization were utilized in this docking study of acetylacetone-based oxindole derivatives to 2,3-dioxygenase indoleamine macromolecules (IDO-1, PDB: 2D0T). The results showed that MarvinSketch provides better binding energy than energy minimization with Open Babel. Molecular docking indicated different interactions between 2D0T macromolecule residues with ligands that have been prepared using MarvinSketch, Open Babel, and without energy minimization.